Elevations in adipocytokines and mortality in rheumatoid arthritis. (23rd March 2022) - Baker, Joshua F; England, Bryant R; George, Michael D; Wysham, Katherine; Johnson, Tate; Kunkel, Gary; Sauer, Brian; Hamilton, Bartlett C; Hunter, Carlos D; Duryee, Michael J; Monach, Paul; Kerr, Gail; et al.
Abstract: Objectives: This study assessed whether circulating levels of adiponectin and leptin are associated with higher mortality in patients with RA. Methods: Participants were adults from the Veterans Affairs RA Registry. Adipokines and inflammatory cytokines were measured as part of a multi-analyte panel on banked serum at enrolment. Dates and causes of death were derived from the Corporate Data Warehouse and the National Death Index. Covariates were derived from medical record, biorepository and registry databases. Multivariable Cox proportional hazard models evaluated associations between biomarkers and all-cause and cause-specific mortality. Results: A total of 2583 participants were included. Higher adiponectin levels were associated with older age, male sex, white race, lower BMI, autoantibody seropositivity, radiographic damage, longer disease duration, prednisone use and osteoporosis. Higher adiponectin concentrations were also associated with higher levels of inflammatory cytokines but not higher disease activity at enrolment. Leptin was primarily associated with greater BMI and comorbidity. The highest quartile of adiponectin ( vs lowest quartile) was associated with higher all-cause mortality [hazard ratio (HR): 1.46 (95% CI: 1.11, 1.93), P = 0.009] and higher cardiovascular mortality [HR: 1.85 (95% CI: 1.24, 2.75), P = 0.003], after accounting for covariates. Higher leptin levels were also associated with greater all-cause and cancer mortality. Conclusions: Elevations in adipokines are associated with age, BMI, comorbidity and severe disease features in RA and independently predict early death. Associations between adiponectin and inflammatory cytokines support the hypothesis that chronic subclinical inflammation promotes metabolic changes that drive elevations in adipokines and yield adverse health outcomes.